PENGARUH BISNIS ONLINE MELALUI E-COMMERCE DI ERA DIGITAL - Nazla Al Fahra; Jorgey Manurung; Elisabeth Pasaribu (PT. Saha Kreasi Indonesia, 2025)
In the digital era, the development of technology and the internet drives rapid business growth by opening access to a wider market and increasing operational efficiency. Global competition demands business people to continue to innovate and utilize technology, including big data and sentiment analysis, to understand changes in the business ecosystem. Research on the influence of online business through e-commerce is carried out using qualitative methods, such as online data analysis, literature studies obtained from google scholar, and also monitoring from social media. E-commerce as a new business model allows online buying and selling transactions without geographical boundaries. However, this progress also presents challenges such as data security, rapid technological changes, and increasingly fierce competition.